2015
DOI: 10.1038/srep11130
|View full text |Cite
|
Sign up to set email alerts
|

HIV Subtypes B and C gp120 and Methamphetamine Interaction: Dopaminergic System Implicates Differential Neuronal Toxicity

Abstract: HIV subtypes or clades differentially induce HIV-associated neurocognitive disorders (HAND) and substance abuse is known to accelerate HIV disease progression. The HIV-1 envelope protein gp120 plays a major role in binding and budding in the central nervous system (CNS) and impacts dopaminergic functions. However, the mechanisms utilized by HIV-1 clades to exert differential effects and the methamphetamine (METH)-associated dopaminergic dysfunction are poorly understood. We hypothesized that clade B and C gp12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Pain researchers have been interested in the role of glia in the regulation of pain since 1991, when Garrison and colleagues noticed an elevated GFAP staining density in chronic pain state, an event that was correlated with hyperalgesia and indicated astrocyte participation in peripheral nerve injury-induced neuropathy (Garrison et al, 1991). Serious injuries and not minor acute pains are able to stimulate dynamic alterations in glial cell functioning (Samikkannu et al, 2015).…”
Section: Pain and Glial Cellsmentioning
confidence: 99%
“…Pain researchers have been interested in the role of glia in the regulation of pain since 1991, when Garrison and colleagues noticed an elevated GFAP staining density in chronic pain state, an event that was correlated with hyperalgesia and indicated astrocyte participation in peripheral nerve injury-induced neuropathy (Garrison et al, 1991). Serious injuries and not minor acute pains are able to stimulate dynamic alterations in glial cell functioning (Samikkannu et al, 2015).…”
Section: Pain and Glial Cellsmentioning
confidence: 99%
“…For example, conditioned-media from HIV-infected human macrophages is more potently neurotoxic to both rat and human neurons in groups from clade B HIV-1 than from clade C HIV-1 (71). A recent study addressing the neurotoxic mechanisms between clade B and clade C HIV gp120 demonstrated that the dopamine system is preferentially affected by HIV gp120 B but not by gp120 C (72). Specifically, clade B gp120 appears to promote neurotoxicity by impairing the expression of dopamine receptors (DRD-2), dopamine transporters (DAT), and the signaling proteins calcium/calmodulin kinases (CaMK) type 2 and 4 in astrocytes when compared to gp120 from clade C (72).…”
Section: Hiv-1 Gp120 Tropism and The Severity Of Neurovirulence And Nmentioning
confidence: 99%
“…A recent study addressing the neurotoxic mechanisms between clade B and clade C HIV gp120 demonstrated that the dopamine system is preferentially affected by HIV gp120 B but not by gp120 C (72). Specifically, clade B gp120 appears to promote neurotoxicity by impairing the expression of dopamine receptors (DRD-2), dopamine transporters (DAT), and the signaling proteins calcium/calmodulin kinases (CaMK) type 2 and 4 in astrocytes when compared to gp120 from clade C (72). Of particular interest, the downregulation of dopamine system proteins was synergistically induced by concomitant treatment with methamphetamine.…”
Section: Hiv-1 Gp120 Tropism and The Severity Of Neurovirulence And Nmentioning
confidence: 99%
See 2 more Smart Citations